2013
DOI: 10.1111/apa.12155
|View full text |Cite
|
Sign up to set email alerts
|

Newborn oxygen saturation at mild altitude versus sea level: implications for neonatal screening for critical congenital heart disease

Abstract: At MA, SpO2 is approximately 0.4% lower compared with SL. Our study supports the AAP recommendation suggesting algorithm cut-offs may need adjustment in high-altitude nurseries and suggest broadening it to MA as well.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
1
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 20 publications
1
18
1
1
Order By: Relevance
“…Samuel 21 found average preductal functional saturations of 97.86% to 98.49% with a 2 SD range encompassing 94.7% to 100% from 2559 feet (780 m). Thilo et al 16 found term postductal saturations of 92% to 93% with a range of 80% to 98% and a 2 SD value of 85% in Denver (5280 feet/1610 m); however, they used fractional saturation technology, and saturation results in their study are likely lower secondary to this.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Samuel 21 found average preductal functional saturations of 97.86% to 98.49% with a 2 SD range encompassing 94.7% to 100% from 2559 feet (780 m). Thilo et al 16 found term postductal saturations of 92% to 93% with a range of 80% to 98% and a 2 SD value of 85% in Denver (5280 feet/1610 m); however, they used fractional saturation technology, and saturation results in their study are likely lower secondary to this.…”
Section: Discussionmentioning
confidence: 99%
“…F, foot; RH, right hand. e566previous studies 14,15,21 and add strength to this data pool by including such a large sampling of infants.…”
Section: Figurementioning
confidence: 99%
“…Newborn measurements were obtained from a reanalysis of data obtained in a previous study that we published elsewhere. 12 Briefly, data collected from newborns aged 25-67 hours who were born either at the Shaare Zedek Medical Center, Jerusalem, Israel (760 m above sea level) or at the Lis Maternity Hospital, Tel Aviv, Israel (sea level) were analyzed. Only healthy, term, appropriate for gestational age newborns of nonsmoking mothers were enrolled.…”
Section: Met Hod Smentioning
confidence: 99%
“…However, research is currently being conducted to determine if screening algorithms should be adjusted, based on elevation. There is evidence that alternative algorithms are warranted at moderate altitudes (2500–5500 feet) [Samuel et al 2013; Wright et al 2014). …”
Section: Resultsmentioning
confidence: 99%